Insects Killer - Odeh, Aladdin; Masood, Abdul-Aziz (My University, 2017)
Insects are a nuisance that usually spreads in the summer. Although some insects are harmless, there are a large number of them that may cause death. So, it's good to have a robot search for insects and get rid of them where you are. The project is a Robot. It monitors the space where it is located searching for insects. When it determines the presence of an insect, the robot begins the hunt to eliminate the insect. When the robot reaches the killing scope, the insect is killed using a mechanical hammer synchronized with the release of an insecticide. The user has the ability to control the robot manually using a mobile App. The project will be accomplished using Raspberry Pi connected with a camera to analyze the objects around the robot and determine if they are insects or not. In addition, there is an Arduino connected with the mechanical parts of the robot to control them based on the commands from the Raspberry Pi. Finally, there the mobile App for Android mobiles has been created using Java. At this stage, the project was completed as planned. So that the robot can track the insects and get rid of them, and the user can control the robot manually using the Android App.